William Shakespeare's Romeo + Juliet [videorecording (Blu-Ray)] - Luhrmann, Baz; Pearce, Craig (Screenwriter); Danes, Claire, 1979-; DiCaprio, Leonardo; Leguizamo, John; Dennehy, Brian; Postlethwaite, Pete; Sorvino, Paul; Venora, Diane; McAlpine, Donald M.; Hooper, Nellee; Barrett, Kym; et al. (Twentieth Century Fox Home Entertainment, 2010)
The original star-crossed lovers light up the screen against a thumping soundtrack and a boldly imagined modern-day setting.